2017
DOI: 10.1515/math-2017-0029
|View full text |Cite
|
Sign up to set email alerts
|

Learnheuristics: hybridizing metaheuristics with machine learning for optimization with dynamic inputs

Abstract: This paper reviews the existing literature on the combination of metaheuristics with machine learning methods and then introduces the concept of learnheuristics, a novel type of hybrid algorithms. Learnheuristics can be used to solve combinatorial optimization problems with dynamic inputs (COPDIs). In these COPDIs, the problem inputs (elements either located in the objective function or in the constraints set) are not fixed in advance as usual. On the contrary, they might vary in a predictable (non-random) way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(75 citation statements)
references
References 128 publications
0
63
0
4
Order By: Relevance
“…Audience members suggested that one direction of future work might be to integrate heuristics with machine learning and other artificial intelligence methods. Through the information gathered and generated by these computational methods, assistance may be provided to a heuristic search process through the dynamic tuning of parameters and through a reduction in the solution space searched [40]. Efforts along these lines may be of benefit to the suggestions we posed for future research in Section 2.4.…”
Section: Discussionmentioning
confidence: 99%
“…Audience members suggested that one direction of future work might be to integrate heuristics with machine learning and other artificial intelligence methods. Through the information gathered and generated by these computational methods, assistance may be provided to a heuristic search process through the dynamic tuning of parameters and through a reduction in the solution space searched [40]. Efforts along these lines may be of benefit to the suggestions we posed for future research in Section 2.4.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the extracted knowledge, which is usually represented by a model or rules, is used to tune or substitute for a component of an optimisation algorithm. Multiple overviews have recently covered the interactions between ML and metaheuristics [33,39,84,197], however, to the best of our knowledge, there is no survey presenting a categorisation on the way that ML is used for enhancing hyper-heuristics. In addition, ML techniques can also be used to choose the best performing algorithm for a particular optimisation problem.…”
Section: Machine Learning For Optimisationmentioning
confidence: 99%
“…To tackle these problems, ML techniques have been used to accelerate the search process and improve the quality of solutions. There are several previous review works about improving metaheuristics by ML [33,39,84,197]. They provided similar taxonomies and one of them proposed in [84] depended on three different criteria, namely localisation, aim and kind of knowledge.…”
Section: Machine Learning For Metaheuristic Optimisationmentioning
confidence: 99%
See 1 more Smart Citation
“…These types of modifications correspond to small modifications of the algorithm since the operating mechanism of the algorithm is not altered. However, many optimization problems cannot be efficiently addressed by an algorithm through modification of its parameters and require deep modifications that alter its mechanism of operation [17,26]. A strategy that has strengthened the results of metaheuristic algorithms has been the hybridization of these with techniques that come from the same and the other areas.…”
Section: Introductionmentioning
confidence: 99%